Does teenage pregnancy and childbirth really increase risk?: exploring outcomes through secondary analysis of NHS data - Watts, Kim (2010)
This retrospective cohort study, examined pregnancy and birth related outcomes for 32,895 births between 1st January 1992 and 31st December 2001 in two maternity units in the East Midlands.